2012
DOI: 10.1186/1742-2094-9-229
|View full text |Cite
|
Sign up to set email alerts
|

Expression of myeloid differentiation factor 88 in neurons is not requisite for the induction of sickness behavior by interleukin-1β

Abstract: BackgroundAnimals respond to inflammation by suppressing normal high-energy activities, including feeding and locomotion, in favor of diverting resources to the immune response. The cytokine interleukin-1 beta (IL-1β) inhibits normal feeding and locomotor activity (LMA) via its actions in the central nervous system (CNS). Behavioral changes in response to IL-1β are mediated by myeloid differentiation factor 88 (MyD88) in non-hematopoietic cells. It is unknown whether IL-1β acts directly on neurons or requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 31 publications
0
26
1
Order By: Relevance
“…The data from our previous work and that from other groups demonstrates a unique role for hypothalamic MyD88 signaling in the illness response to several important PAMPs, and in the inflammatory amplification and cytokine signaling observed in the hypothalamus during systemic inflammation 17 31 . Furthermore, in vitro stimulation of TLR3KO microglia with poly (I:C) results in substantial cytokine release and activation of downstream MAPK signaling, albeit with delayed kinetics relative to WT microglia 24 .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The data from our previous work and that from other groups demonstrates a unique role for hypothalamic MyD88 signaling in the illness response to several important PAMPs, and in the inflammatory amplification and cytokine signaling observed in the hypothalamus during systemic inflammation 17 31 . Furthermore, in vitro stimulation of TLR3KO microglia with poly (I:C) results in substantial cytokine release and activation of downstream MAPK signaling, albeit with delayed kinetics relative to WT microglia 24 .…”
Section: Discussionmentioning
confidence: 62%
“…Prior studies demonstrate that in response to both peripheral and central immune challenge, a pro-inflammatory response is generated within the CNS, with particularly robust inflammation noted within the MBH 15 16 18 31 . In particular, the local expression and release of IL-1β within the hypothalamus is critical for the induction of sickness behaviors 1 17 .…”
Section: Resultsmentioning
confidence: 99%
“…A number of previous studies have found that TLRs in the spinal cord played an important role in the model of neuropathic pain and nerve injury, in which microglia and astrocytes produced proinflammatory cytokines by activating TLRs [1820]. Nociceptors of DRG that express TLRs or IL-1R are also activated by LPS or inflammatory cytokine interleukin-1β, inducing pain hypersensitivity [5, 1822]. Recent publications show that MyD88, adaptor protein of TLRs and IL-1R, is also found in the expression in DRG and spinal cord [1820].…”
Section: Introductionmentioning
confidence: 99%
“…Sickness responses are coordinated sets of adaptive behavioral changes including loss of appetite, hypoactivity, and hyperthermia during the course of human diseases such as cancer, acquired immune deficiency syndrome (AIDS), tuberculosis, and renal failure 4 . Although hypothalamic inflammation has been recognized as a prominent component of sickness responses 5 6 , the pathophysiologic mechanisms of sickness symptoms are poorly understood.…”
mentioning
confidence: 99%